2023
DOI: 10.1155/2023/1040478
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Antioxidant, Antimicrobial, and Antibiofilm Activities of Essential Oils of Plumeria alba (Forget-Me-Not)

Abstract: Essential oils are known to possess many biological properties such as antimicrobial and antioxidant activities. Plumeria alba flowers are used in traditional remedies for diarrhea, cough, fever, and asthma treatment. This work evaluated the chemical composition and the biological activities of essential oils obtained from the flowers and leaves of Plumeria alba. The essential oils were extracted using the Clevenger-type apparatus and characterized using GC-MS. In the flower essential oil, a total of 17 compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Linalool has demonstrated antioxidative properties in a study from Plumeria alba [ 38 ]. The essential oils from this plant have been shown to have antioxidant properties.…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Linalool has demonstrated antioxidative properties in a study from Plumeria alba [ 38 ]. The essential oils from this plant have been shown to have antioxidant properties.…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…Gas Chromatography-Mass Spectroscopy studies identified that linalool composes about 24% of the active essential oil. The samples prepared from the plants flowers gave IC 50 values of 370, 1014, and 1943 μg/mL for the H 2 O 2 scavenging assay, DPPH radical scavenging assay, and thiobarbituric acid reactive substances (TBARS) assay respectively [ 38 ]. In addition, in vivo studies in hemiparkinsonian rat models indicated neuroprotective effects.…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…& L. M. Perry (clove) leaf, suppressed the biofilm formation of an oral anaerobe Porphyromonas gingivalis [105]. The essential oil extracted from the leaves and flowers of Plumeria alba displayed good potential to inhibit the formation of Pseudomonas aeruginosa biofilms [106]. Most of the biofilm inhibitors are isolated from natural sources; some synthetic compounds, enzymes and chelating agents also possess anti-biofilm activity.…”
Section: Inhibition Of Biofilmmentioning
confidence: 99%